To solve the equation \( (13x - 2)(x - 34) = 0 \), we can use a cool rule called the zero product property. This means that if you multiply two things and get zero, then at least one of those things must be zero!
So, we can set each part (or "factor") equal to zero:
- \( 13x - 2 = 0 \)
- \( x - 34 = 0 \)
Now, let’s solve each one step by step!
For the first part:
\[ 13x - 2 = 0 \]
To get rid of the -2, we add 2 to both sides:
\[ 13x = 2 \]
Next, we want to find out what \( x \) is. Since \( x \) is being multiplied by 13, we need to divide by 13:
\[ x = \frac{2}{13} \]
For the second part:
\[ x - 34 = 0 \]
This one is pretty easy! We just add 34 to both sides to solve for \( x \):
\[ x = 34 \]
So, the answers to the equation \( (13x - 2)(x - 34) = 0 \) are:
\[ x = \frac{2}{13} \quad \text{and} \quad x = 34 \]
That's it! We found that \( x \) can be \( \frac{2}{13} \) or \( 34 \).